Electronic and magnetic properties of Half Heusler alloy NiCrSi - Manandhar, Bishartha; Dahal, Prem Sagar; Nepal, Sashi; Baral, Anisha (Himalayan Journal of Science and Technology, 2022)
Utilizing the Quantum Espresso Package and the plane wave pseudopotential approach, the electrical and magnetic characteristics of the Half Heusler alloy NiCrSi have been investigated.Ultrasoft pseudo-potential is used for this calculation. Through our calculation, it was revealed that NiCrSi is a half-metallic ferromagnet in nature with a bandgap of 0.81eV and an effective moment of 2µB respectively. The origin of the gap is mainly due to the covalent band gap and d-d band gap in the system separating bonding states from anti-bonding states. Our calculation predicts a larger spin moment at Cr site than at Ni site which is antiparallel to the moment of Si. The hybridization of Ni- 3d and Cr-4d states can open a minority spin gap at Ef resulting in the semi-conducting nature of the minority spin band.